I Want It All and I Want It Now. Motivations of Counterfeit Luxury Consumption Among Gcc Consumers - Pueschel, Julia (Management international / International Management / Gestiòn Internacional, 2020)
This research investigates the motivations of counterfeit luxury consumption in the Gulf Cooperation Council (GCC) countries. Using a Means-End Chain approach, this research uncovers four dominant motivational patterns and complexities that drive affluent GCC consumers to purchase counterfeit luxury products: Value-Consciousness, Belonging, Hedonism and Self-esteem. Luxury brands and policy makers could use these main hidden final values to gain a holistic understanding of consumer motivations and develop stronger anti-counterfeiting strategies to discourage counterfeit consumption.